Diagnostic usefulness of technetium-99m-pertechnetate SPECT in a patient with Meckel’s diverticulum - Gülbanu Erkan; Mehmet Çoban; Aysun Çalışkan; Duygu Tokbay; Bülent Değertekin; Süleyman Özdemir; Emel Öztürk; Handan Doğan; Ömür Ataoğlu (Turkish Journal of Gastroenterology, 2019)
-